Motivational Factors Influencing the Publication of Research article by Faculty Members of the Faculty of Management Sciences, Chiang Mai Rajabhat University - Phunataphon, Rapichaya; Kitthitinan, Phathranit (Research and Development Journal, Loei Rajabhat University, 2025)
This quantitative research aimed to investigate the motivational factors influencing the publication of research articles by faculty members of the Faculty of Management Sciences, Chiang Mai Rajabhat University. Data was collected through questionnaires distributed to a total of 70 faculty members. Analyzed using descriptive statistics to calculate percentages and means, while inferential statistics, were applied through multiple linear regression analysis. The research findings revealed that the majority of the faculty members were female, aged between 41- 45 years, graduated with a master's degree in Thailand. Most of them had 11-20 years of teaching experience, 1-5 years of research experience, and had published, on average, one research article in both national and international journals, but did not yet hold any academic positions. The analysis of motivational factors influencing research article publication indicated that only the factor of career advancement significantly affected the publication of research articles by faculty members of the Faculty of Management Sciences, Chiang Mai Rajabhat University.